2015
DOI: 10.1371/journal.pone.0116377
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Coronary Artery Calcium Testing for Coronary Heart and Cardiovascular Disease Risk Prediction to Guide Statin Allocation: The Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: BackgroundThe Multi-Ethnic Study of Atherosclerosis (MESA) showed that the addition of coronary artery calcium (CAC) to traditional risk factors improves risk classification, particularly in intermediate risk asymptomatic patients with LDL cholesterol levels <160 mg/dL. However, the cost-effectiveness of incorporating CAC into treatment decision rules has yet to be clearly delineated.ObjectiveTo model the cost-effectiveness of CAC for cardiovascular risk stratification in asymptomatic, intermediate risk patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…25 Two prominent studies have shown that using CAC testing is more cost effective than the current widespread statin use that is advocated by the ACC/AHA pooled cohort equations or "treat all" strategies. 26 It has outperformed risk factor based paradigms such as the Framingham Risk Score (FRS), 3 the European Society of Cardiology Score 4 and the 2013 AHA/ACC Pooled Cohort Equations, 5 and, in 3 prospective, population-based outcome trials demonstrated an extremely high net reclassification index (NRI) of the FRS, ranging from 52% to 66% in the intermediate risk group. 16,27,28 The inclusion of CAC in guidelines is summarized in Table 2.…”
Section: Evidence Supporting Cac For Risk Assessmentmentioning
confidence: 99%
“…25 Two prominent studies have shown that using CAC testing is more cost effective than the current widespread statin use that is advocated by the ACC/AHA pooled cohort equations or "treat all" strategies. 26 It has outperformed risk factor based paradigms such as the Framingham Risk Score (FRS), 3 the European Society of Cardiology Score 4 and the 2013 AHA/ACC Pooled Cohort Equations, 5 and, in 3 prospective, population-based outcome trials demonstrated an extremely high net reclassification index (NRI) of the FRS, ranging from 52% to 66% in the intermediate risk group. 16,27,28 The inclusion of CAC in guidelines is summarized in Table 2.…”
Section: Evidence Supporting Cac For Risk Assessmentmentioning
confidence: 99%
“…[40][41][42] This may be helpful as surrogate endpoints for intervention studies, as well as potentially add to global CVD risk assessment and guide treatment decisions. [43][44][45][46][47] Subclinical atherosclerosis is commonly assessed by carotid intima-media thickness (cIMT), coronary artery calcium score (CACS), coronary computed tomography angiography (CCTA) and cardiac magnetic resonance imaging (CMR). [5,[46][47][48][49][50][51][52][53][54][55][56][57][58] In recent years, some groups have started to evaluate these imaging techniques in former preeclampsia patients, as discussed below.…”
Section: Cardiovascular Imagingmentioning
confidence: 99%
“…The total incidence of adverse reactions of patients with coronary heart disease in the observation group of patients with coronary heart disease was significantly reduced (3.08%) compared with that in the control group (18.46%) (P<0.05). These findings proved that in the treatment of patients with coronary heart disease, statins could regulate the blood lipid level and myocardial cell autorhythmicity, increase the vascular endothelial function, stabilize the coronary atherosclerotic plaque, and resist the inflammation of myocardial cell and oxidation [9,10]. As a result, the patients' condition and the life quality of patients with coronary heart disease were significantly improved.…”
Section: Discussionmentioning
confidence: 88%